Alat Pengatur Suhu pada Mesin Penetas Telur Ayam menggunakan Mikrokontroler, Android dan Server AWS (Amazon Web Service) - Muhammad Fajri; Hidra Amnur; Aldo Erianda (SOTVI - Society of Visual Informatics, 2020)
IoT technology is currently very developed. Usually the chicken incubates the eggs naturally by the mother. but at this time many egg incubators have been produced. incubating eggs made by humans can be done with a very large number of eggs. Both of these incubation techniques have their respective advantages and disadvantages. Among these machines, the heat setting of the machine is still manual, namely by checking the temperature periodically so that it is not too hot or too hot to hatch the eggs and it will be very draining. Egg incubators that are widely circulating today are more wasteful of electricity, because the use of lights on these tools is not controlled so that they will continue to burn and will use a lot of electricity. This research project makes a tool to hatch eggs and keep the temperature stable. A tool that can adjust the temperature automatically and send the data to the user. Send the data that has been collected from the sensor to the user via the nodeMCU microcontroller. And can monitor the state of the egg hatching device via Andrioid user who has sent data from the device and stored in the database then sent to the server.